Effect of aerobic versus resisted exercise on blood coagulation in chronic kidney disease patient - Walaa Mohammed Mohammed Mohammed; Awny Fouad Rahmy; Ehab Fawzy Abdaelziz; Heba Ali Abdelgfhafar (Cairo : Walaa Mohammed Mohammed Mohammed, 2021)
Background: Patients with chronic kidney disease ( CKD) often present higher levels of traditional risk factors for thromboembolic events, such as hypertension, diabetes, obesity and dyslipidaemia; these factors also affect the coagulation system Objective: to investigate the effect of aerobic exercises versus resistive exercise on blood coagulation in chronic kidney disease stage 2,3. Subjects and methods: Sixty male patients with chronic kidney disease stage 2, 3 were participated in study, their age range from 40 to 50 years old and selected from Elta El kabir hospital Al Ismailia Governrate. they was randomly assigned into equal Group(A&B). Group A was received aerobic exercise while Group B was received resisted exercise. Both groups was received Three sessions per week for 4 months. Measurements were measure twice, before and after treatment :laboratory measure :weight , fibrinogen level, prothrombin time, INR(International Normalized Ratio) and platlets account , physical therapy measure 6 min walk test and Quality of life by short form health {u2013}related (SF-36). Results: The results showed that there was significant improvement in weight, platelets count ,fibrinogen level, Prothrombin time ,INR(International Normalized Ratio) ,quality of life and 6 minute walk test in both groups after treatment while there was no significant difference between two groups after treatment
Thesis (Ph.D.) - Cairo University - Faculty of Physical Therapy - Department of Physical Therapy for Cardiopulmonary and Geriatrics Disorder
Issued also as CD
Keywords: Aerobic exercises; Chronic kidney disease; Resisted exercise